MEMPERBAHARUI FILOSOFI BEKERJA DALAM MENANGKAL BUDAYA KEMALASAN - Halawa, Ririn Valentina (P3M STT Kristus Alfa Omega, 2023)
Humans in their daily lives spend one-third of their time working. The purpose of working is to fulfil the needs of life. The method used in making this article is the method of text analysis and literature review. Work is a basic human need like food, beauty, rest, friendship, prayer, and sexuality that is not only medicine but food for the human soul. Without meaningful work, humans feel significant loss and inner emptiness. People who stop working for physical or other reasons quickly discover how much they need work to thrive emotionally, physically, and spiritually. Thus, the author offers that to understand the meaning of work according to 2 Thessalonians 3:6-12, humans need to fortify themselves from laziness